Source areas of the Eastern Ebro Valley loess (NE Iberian Peninsula): Heavy mineral composition as a provenance indicator. Issue 15 (30th September 2022) - Plata, José M.; Balasch, Josep Carles; Rodríguez, Rafael; Boixadera, Jaume; Castelltort, Xavier; Olarieta, José Ramón; Antúnez, Montserrat; Poch, Rosa M.
Abstract: Loess deposits of the Eastern Ebro Valley (NE Iberian Peninsula) occupy an area of ~2000 km 2 mostly on the east of the Ebro depression and locally in the Móra Basin. We studied 38 samples of loess and 47 samples of their possible source areas, in order to determine the location of the origin of the loess materials, based on their particle size distribution and composition of heavy minerals. Our results clearly differentiate two depositional loess basins disconnected by the reliefs of the Pre‐Coastal Range with different mineralogical signatures: the Ebro Basin and the Móra Basin. The most relevant variables to discern source areas were the percentage of heavy minerals, the concentrations of zircon, staurolite, rutile and inosilicates, and the presence of gypsum. In the Ebro Basin, the largest set of loess deposits is located around a depocenter in the Batea region and along several lateral areas, with materials that come from the central alluvial plain of the Middle Ebro River (25 to >100 km travel distance), in addition to deflated materials from Miocene interfluvial substrates. On the other hand, loess deposits of the Móra Basin come from more proximal source areas (<15 km), originating from the alluvial materials of the Lower Ebro River that contain the contributions of its tributaries, the Cinca and Segre rivers. Taking into account the homogeneity in the mineralogical composition of complex loess sequences, we deduced a general WNW–ESE wind direction, which would have remained constant over the last two cold periods (MIS‐2 and MIS‐6). Along this axis, the Pàndols–Cavalls Range, with a height difference of 200–350 m, acted as a wind barrier separating the loess of Ebro Basin from the loess of Móra Basin. Abstract : The loess provenance areas of the Ebro and Móra basins are mainly the fluvial terraces of the Middle and Lower Ebro River, respectively, according to the analyses of very heavy minerals and particle size. The wind transport distances are relatively short (<100 km). The two basins are separated by a topographical range acting as a wind barrier.